Creation or evolution do we have to choose? - Alexander, Denis R. (Oxford Monarch, 2008)
In this brilliant and highly readable treatise, Denis Alexander the scientist-believer argues convincingly and lovingly that a committed Christian need not fear evolution, but can embrace it as God's awesome means of creation.'
Includes bibliographical references and index
Keywords: Creationism; Evolution (Biology) -- Religious aspects -- Christianity; Creation